Development of an Air-Bearing Testbed for Nanosatellite Attitude Determination and Control Systems - Pablo Raul Yanyachi; Alfredo Mamani-Saico; Xinsheng Wang; Brayan Espinoza-Garcia (IEEE Access, 2024)
A testbed that simulates space conditions in a terrestrial laboratory is essential for evaluating, verifying, and teaching attitude control in nanosatellites. The control methodology applied dictates the configuration of each testbed, and highlights the need for an appropriate system for such tests. This study presents the development and validation of a spherical testbed designed to simulate the space environment, which includes a decentralized architecture ADCS module. This architecture allows for reduced time between the Model-in-the-Loop and Hardware-in-the-Loop phases, as well as facilitating high-level programming for evaluating attitude control algorithms based on reaction wheels. To validate the testbed, both point-to-point and tracking maneuvers were implemented and evaluated using the following algorithms: traditional PID control, feedback control, and a robust adaptive controller developed by Boskovic. Additionally, the system’s mathematical model was constructed, and its validity was confirmed through maximum likelihood estimation of the equation-error using the controller results. The findings demonstrate the effectiveness of this testbed, which is both extendable and accessible for evaluating reaction wheel-based attitude control algorithms. However, the study also identifies limitations and outlines directions for future work. Notably, in ground-based tests, the torques generated by gravity gradient are unknown and difficult to counteract, complicating the control of the roll and pitch axes.